Language Politeness Strategies of English Teachers In The Mandar Community - Umar Umar (Indonesia Prime, 2021)
Language politeness is very important in education, such as in classroom teaching and learning practices. During the teaching and learning process the teacher uses speech a lot to communicate with students showing politeness strategies. Considering language politeness, consists of strategies to make appropriate politeness in communication situations between students and teachers. Certainly in society, like in the classroom, politeness needs to be applied because politeness creates conflict between teachers and students. This means that politeness is used in classroom interactions in order to build a good relationship between teachers and students. Besides that. The politeness of the teacher's language is very helpful in motivating students to learn. In this study, the researcher analyzed the language politeness strategies used by the teacher and students in learning in the classroom. The purpose of this study was to find out the language politeness strategies used by English teachers in motivating students to learn in the Mandar Community. This study uses Brown's and S.C Levinson theory of politeness strategies for supporting this research. This study used qualitative methods to analyze data and explain English teacher politeness strategies in motivating students to learn which are used in daily conversation. The data sources of this study were English teachers and students in Alu disctrict Polewali Mandar regency. The instrument used in this research is observation From several conversational analyzes, several phenomena were found to be non-universal in the theory of B&L politeness, including the S&S theory in speaker conversations conducted by teachers and students in the Mandar language community carried out in several places and by several speakers. The theory assumes that the form of politeness strategy chosen by speech participants when interacting in the speaker's position as superior or superior to subordinates that occurs between school principals and teachers does not show a more casual speech pattern for school principals or more polite for teachers. caused by other factors such as friendship between the principal and teachers and seniority factors